Spiritual leadership among nurses in hospitals: A scoping review - Fadly, Muhammad; Bhakti, Wida Kuswida; Ramadhaniyati; Imran (JOURNAL OF Mental Health Concerns, 2026)
Background: Spiritual leadership plays a critical role in service management within psychiatric hospitals. However, psychiatric nurses’ implementation of spiritual leadership in nursing care remains very limited. Purpose: To map and identify previous research findings regarding the implementation of spiritual leadership among nurses working in psychiatric hospitals. Method: This scoping review was conducted through a systematic search of three databases: PubMed, Scopus, and ScienceDirect. The selection criteria focused on studies published in Indonesian and English between 2015 and 2025. Inclusion criteria encompassed quantitative, qualitative, and mixed-methods studies discussing spiritual leadership among nurses in hospitals. Results: The search results indicated that five articles met the inclusion criteria. The key finding is that spiritual leadership is not merely about religious aspects, but rather about fulfilling fundamental human needs for meaning in life and a sense of belonging in the workplace. Furthermore, spiritual leadership is effective in reducing turnover rates by mitigating emotional stress and exhaustion resulting from extreme workloads. Conclusion: Healthcare institutions are advised to integrate spiritual leadership training into staff development programs and organizational policies to create a more holistic and emotionally competent care system. Keywords: Hospital; Nurses; Spiritual Leadership.